Fintech sebagai Solusi Inovatif untuk Meningkatkan Efisiensi dan Aksesibilitas Layanan Keuangan Syariah - Vika Mariska (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The rapid development of financial technology (fintech) provides innovative solutions to improve efficiency and accessibility in the Islamic finance sector. Islamic finance, based on Islamic principles, faces challenges in financial inclusion, high operational costs, and limited access to financial institutions. This study aims to explore the application of fintech as a solution to these issues. The research method used is literature review and qualitative analysis of various fintech models based on sharia principles, such as peer-to-peer lending, crowdfunding, and digital payments. The results indicate that fintech has significant potential in enhancing operational efficiency and expanding accessibility to sharia-compliant financial services. By utilizing technologies such as mobile applications and blockchain, fintech can reduce transaction costs and offer solutions for underserved communities. However, challenges related to sharia compliance and clear regulations need to be addressed to ensure the successful implementation of fintech in this sector.